2020
DOI: 10.1177/1078390320902834
|View full text |Cite
|
Sign up to set email alerts
|

Spirituality in Psychiatric Nursing: A Concept Analysis

Abstract: BACKGROUND: There is robust literature on spirituality in nursing. Despite the unique needs of those with serious mental illness, there has been little exploration of spirituality in the context of nursing care for this population. Lacking a well-defined concept of spirituality in psychiatric care, mental health nurses often struggle to provide optimal, holistic care. OBJECTIVE: The aim of this concept analysis was to review definitions and descriptions of spirituality in the psychiatric nursing literature to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 43 publications
0
9
0
2
Order By: Relevance
“…Understanding which role religion plays in the life of the caregiver is a piece of valuable information. The improved coping is a result of addressing spirituality in psychiatric nursing practice (Clark & Emerson, 2021).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Understanding which role religion plays in the life of the caregiver is a piece of valuable information. The improved coping is a result of addressing spirituality in psychiatric nursing practice (Clark & Emerson, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…As so, spirituality may represent a critical dimension in living and overcoming this situation. Spirituality in psychiatric nursing, according to a concept analysis, is a result of value-influenced thinking and the capability for interaction with others (Clark & Emerson, 2021).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…From this point of view, spirituality is an intrinsic motivation to seek satisfaction and maintain a harmonious relationship with oneself/others in times of stress or crisis (20)(21)(22)(23). Studies that have examined spirituality during COVID-19 have found that it can facilitate self-reported self-care, connectedness, and meaning and purpose in life (18,24,25).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Ebenso wie das DGPPN-Positionspapier [ 29 ] versteht die Mehrheit der Literatur Sp als den im Vergleich zu R umfassenderen Begriff. Eine pflegewissenschaftliche Konzeptanalyse [ 5 ] subsummiert Sp als das wertebasierte Denken der Patienten, ihre Fähigkeit zur Interaktion mit anderen, ihre Suche nach Lebenssinn und Verbundenheit („connectedness“) mit anderen Menschen und mit dem transzendenten Heiligen. Psychiatrisches SpC könne tröstliche Effekte haben und das Coping der Patienten fördern.…”
Section: Diskussionunclassified